2021
DOI: 10.3390/land10030328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Fertilizer on Soil Bacteria in Maize Fields

Abstract: Soil microorganisms play an important role in agricultural ecosystems, but their response to organic fertilizer application has not been thoroughly elucidated. Thus, high-throughput sequencing was used to investigate the responses of soil bacterial to organic fertilizer amendment (composted from pig manure) in the field during the entire growth cycle of maize plants. Four treatments were studied: treatment with 2 kg·m–2 organic fertilizer application (OF_2), treatment with 4 kg·m–2 organic fertilizer applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
2
16
0
2
Order By: Relevance
“…Fertilization affects soil microbial diversity by altering the nutrient concentration of the soil [247]. Fertilizer application affects the development of disease, alters the bacterial community composition and function [248][249][250][251], and contributes towards the formation of soil microbial biomass [252]. In agriculture, farmers may use either organic and mineral fertilizers, depending on their needs.…”
Section: Fertilizermentioning
confidence: 99%
“…Fertilization affects soil microbial diversity by altering the nutrient concentration of the soil [247]. Fertilizer application affects the development of disease, alters the bacterial community composition and function [248][249][250][251], and contributes towards the formation of soil microbial biomass [252]. In agriculture, farmers may use either organic and mineral fertilizers, depending on their needs.…”
Section: Fertilizermentioning
confidence: 99%
“…At that time, the amount of diazotrophs in the GPM + T sample was quite high in the spring (Figure 3). When manure is used for fertilization, an increase in organotrophs is usually observed first, followed by an increase in the abundance of nitrifiers, and an overall increase in soil activity is also observed [43,44]. Fertilization of manure also affects the taxonomic composition of microorganisms and increases the number of more active bacteria belonging to the taxonomic groups of Actinobacteria and Proteobacteria, which can grow in the nutrient medium [43][44][45].…”
Section: Abundance Of Different Physiological Groups Of Soil Microorg...mentioning
confidence: 99%
“…When manure is used for fertilization, an increase in organotrophs is usually observed first, followed by an increase in the abundance of nitrifiers, and an overall increase in soil activity is also observed [43,44]. Fertilization of manure also affects the taxonomic composition of microorganisms and increases the number of more active bacteria belonging to the taxonomic groups of Actinobacteria and Proteobacteria, which can grow in the nutrient medium [43][44][45]. In our studies, a significant increase in the abundance of nitrifiers was observed in samples fertilized with poultry manure in the autumn (Figure 1).…”
Section: Abundance Of Different Physiological Groups Of Soil Microorg...mentioning
confidence: 99%
“…Penggunaan pupuk organic pada tanaman dapat mencukupi kebutuhan nutrisi serta unsur hara selama tanaman berada pada siklus pertumbuhan. Salah satu upaya dalam mengolah kesuburan tanah dan memperbaiki sifat fisik tanah, biologi tanah yaitu dengan aplikasi pupuk organik seperti kotoran ayam, eceng gondok dan serbuk gergaji (Wu et al, 2021).…”
Section: Pendahuluanunclassified
“…Kotoran ayam memiliki kandungan hara diantaranya P 1,82% N 1,72%, Mn 610%, Fe 3475% K 2,18% Ca 9,23% Mg 0,86% Zn 501% yang cukup tinggi. Unsur pembentuk serbuk gergaji terdiri dari hidrogen (H), oksigen (O), karbon (C), nitrogen (N), abu serta unsur lainnya (Li et al, 2021).Penelitian menggunakan pupuk organic dari berbagai bahan dasar seperti eceng gondok, kotoran ayam, dan serbuk gergaji. Serbuk gergaji dapat digunakan sebagai pupuk organic.…”
Section: Pendahuluanunclassified